Pharmacologic modulation of RNA splicing enhances anti-tumor immunity - Lu, Sydney X; De Neef, Emma; Thomas, James D; Sabio, Erich; Rousseau, Benoit; Gigoux, Mathieu; Knorr, David A; Greenbaum, Benjamin; Elhanati, Yuval; Hogg, Simon J; Chow, Andrew; Ghosh, Arnab; et al. (Cell, 2021)
Although mutations in DNA are the best-studied source of neoantigens that determine response to immune checkpoint blockade, alterations in RNA splicing within cancer cells could similarly result in neoepitope production. However, the endogenous antigenicity and clinical potential of such splicing-derived epitopes have not been tested. Here, we demonstrate that pharmacologic modulation of splicing via specific drug classes generates bona fide neoantigens and elicits anti-tumor immunity, augmenting checkpoint immunotherapy. Splicing modulation inhibited tumor growth and enhanced checkpoint blockade in a manner dependent on host T cells and peptides presented on tumor MHC class I. Splicing modulation induced stereotyped splicing changes across tumor types, altering the MHC I-bound immunopeptidome to yield splicing-derived neoepitopes that trigger an anti-tumor T cell response in vivo. These data definitively identify splicing modulation as an untapped source of immunogenic peptides and provide a means to enhance response to checkpoint blockade that is readily translatable to the clinic.